Escherichia coli Strains of Chicken Intestines: Characterization of Ciprofloxacin and Erythromycin Antibiotic Resistance Profiles - Susilo, Susilo; Setyaningsih, Maryanti; Mulyawati, Dita (Universitas Labuhanbatu, 2022)
Antibiotic resistance has now become a global problem that can endanger livestock. The use of antibiotics as a trigger for the growth of livestock can have an impact on humans. This study investigated the antibiotic resistance of Ciprofloxacin and Erythromycin against Escherichia coli. 14 samples of E.coli were isolated from the intestinal colon of chickens that were kept conventionally by broiler breeders in Yogyakarta. E.coli isolates were cultured on Eosin Methylene Blue Agar (EMB) media for 24 hours at the Bacteriology Laboratory of the Indonesian Veterinary Research Institute (BBLITVET), Bogor, Indonesia. Ciprofloxacin and Erythromycin antibiotic discs were placed on EMB media and then incubated for 24 hours at 37oC. The diameter of the clear zone of inhibition and the zone of resistance inhibition was measured on each repetition using the Clinical and Laboratory Standards Institute (CLSI) standard. The results obtained showed that the antibiotic Erythromycin had higher resistance than Ciprofloxacin. In conclusion, these two antibiotics can be categorized as susceptible or sensitive to E. coli bacteria